On the need to change the methodology of teaching graphic disciplines, taking into account the capabilities of modern computer technologies - Pritykin Федор (Рroblems of engineering and professional education, 2023)
In the article, the sections "Drawing geometry", "Engineering graphics" and "Computer graphics" are linked together. It is shown the necessity of coding of computer technologies in the study of graphics, as well as the need to revise the curriculum. During the lesson, three-dimensional computer modeling was introduced.